Ultrasound contrast microbubbles to predict the microsphere distribution during transarterial radioembolization with holmium microspheres, an in vitro proof of concept study - Jan L. van der Hoek; Tess J. Snoeijink; Hadi Mirgolbabaee; Romaine Kunst; Michel Versluis; Jutta Arens; Srirang Manohar; Erik Groot Jebbink (Drug Delivery)
Transarterial radioembolization (TARE) is an established treatment method for non-resectable liver tumors. One of the challenges of the approach is the accurate prediction of the microsphere biodistribution in the liver. We propose to use ultrasound contrast microbubbles as holmium microsphere precursors, which allows real-time prediction of the microsphere trajectories and biodistribution using dynamic contrast-enhanced ultrasound (DCE-US). The immediate goal in this in vitro study was to investigate the predictive capabilities of microbubbles as microsphere precursors. The study was conducted in an experimental in vitro model which represents the bifurcating right branch of the hepatic artery. A controlled injection of experimental BR-14 ultrasound contrast microbubbles and non-radioactive holmium-165 microspheres was performed in separate consecutive experiments in an arterial flow phantom. The microbubbles and microspheres were collected separately at the outlets of the phantom and counted using a Coulter counter to determine their distribution over the different outlets. The flow profile, the injection velocity, and the catheter position were monitored during the measurements to ensure stability. The results showed a good correlation between the microbubble and the microsphere distributions (p = 0.0038, r = 0.88) measured at the outlets. Differences in the distributions could be attributed to the characteristics of microbubbles and microspheres alone (e.g. particle size and concentration), since critical parameters were kept stable between the two experiments. The current in vitro study provides confidence that the microsphere biodistribution can be predicted using contrast microbubbles. The comparison provided by this study forms a foundation for the development of a DCE-US guided TARE treatment.